1998
DOI: 10.3748/wjg.v4.i5.437
|View full text |Cite
|
Sign up to set email alerts
|

Protection of gastric mucosa from ethanol induced injury by recombinant epidermal growth factor in rats

Abstract: AIM:To determine whether recombinant human epidermal growth factor (rhEGF) can protect gastric mucosa against ethanol induced injury in rats.METHOD: Fifty-four SD rats weighing 200g-500g each were divided into six groups after fasting for 24 hours.Three groups received different doses of oral rhEGF (30, 60 and 120&mgr;gcenter dotkg(-1)center dotd(-1)), one group was given cimetidine,one subcutaneous rhEGF (rhEGF IV) and one received saline as control.RESULTS:Acute gastric dilatation developed in the control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Earlier studies have reported the efficacy of EGF in negating the detrimental effects of the gastric mucosal ulcers both in acute and chronic conditions treated with ethanol [11]. However, these studies are limited at several levels in understanding the cytoprotection and repair mechanism(s) underlying the healing process [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have reported the efficacy of EGF in negating the detrimental effects of the gastric mucosal ulcers both in acute and chronic conditions treated with ethanol [11]. However, these studies are limited at several levels in understanding the cytoprotection and repair mechanism(s) underlying the healing process [18].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the cytoprotective effects of the growth factor such as Epidermal Growth factor (EGF) were effective towards the restoration of lesioned gastro intestinal mucosal integrity both in vivo and in vitro [10]. In line with these reports it has been demonstrated that orally administered EGF ameliorated the gastric and duodenal mucosa injury induced with the ethanol treatment [11]. The Recombinant Human EGF (rhEGF) developed indigenously by Bharat Biotech International Limited has been from expression of a synthetic gene in Escherichia coli similar to the natural EGF with its purity to be 99% assessed by HPLC [12].…”
Section: Introductionmentioning
confidence: 97%
“…Group I served as control, Groups II, III, and IV received oral doses of 50, 100, and 250 mg/kg b.w., and Group V received oral 11.5 mg/kg b.w. of the reference standard drug, cimetidine (Xu et al, 1998). All doses were administered intragastrically with water (10 ml/kg b.w.).…”
Section: Ethanol-induced Gastric Ulcer In Ratsmentioning
confidence: 99%
“…Gentiopicroside administrated orally increased HSP‐70 levels, which may improve gastric mucosa protection. Moreover, EGF and VEGF also contribute to enhancing angiogenesis in gastric mucosa and accelerating healing of ethanol‐induced gastric erosions (Tarnawaski, Sekhon, Ichikawa, & Sarfeh, ; Xu, Gan, Chen, Jiang, & Xu, ). Mice orally administrated with gentiopicroside normalized EGF and VEGF levels, which indicated the effect of gentiopicroside in antagonizing gastric mucosal injury.…”
Section: Discussionmentioning
confidence: 99%